O uso de modelagem no ensino de função exponencial - Brucki, Cristina Maria (2011)
The present work is part of the use of Mathematical Modeling as a teaching strategy. It presents a modeling activity to teach Exponential Fuction and the relation between algebraic model of exponential function with the General Term of Geometric Progression model. The main goal is to analyze the effects of modeling in teaching. The object of the research were high school students of a public school in Sao Paulo. The research is qualitative, developed through participant observation, and the data was collected from the contextualized activities with the use of models. The theoretic referential where modeling conceptions developed by Honei Cerqueira Barbosa and the learning theory developed by Ausubel. The activity were developed using the Geometric Progression as an anchor in the formulation of a Exponential Fuction concept, for a significative learning. As a result, it's observable that the use of modeling in teaching can be practiced in any school, as long as the teacher is willing to do that, but that's not and easy task. That's because it's required that both the teacher and the student are committed to knowledge production. We can also assume that the modelling makes possible a reflexive learning, because the interest and the participation of the student are inherent in this methodology. Besides, we can realized that the modeling has the potential to make the student think critically, because it establishes a relation between mathematical content and real problems